2020
DOI: 10.1016/j.actamat.2019.12.038
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation and growth of η phase in nickel-based superalloy during long-term thermal exposure

Abstract: The microstructure degradation and subsequent phases transformation in Waspaloy nickelbased superalloy during thermal exposure at 780 °C for 10,000 h are investigated. Two paths of η phase formation in the centre of extra-large γ' (EL-γ') following the formation of EL-γ' were observed: (i) η phase directly precipitated within EL-γ' when the coalescence of γ' reached a critical stage; (ii) η phase precipitated at the interface of small size MC carbide and EL-γ', with both MC and η embedded inside EL-γ'. The pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, the η phase Ni 3 (Ti,Nb,Ta) with a D0 24 hexagonal structure is generally regarded as a detrimental phase for the tensile, corrosion and creep-rupture properties. 26,27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the η phase Ni 3 (Ti,Nb,Ta) with a D0 24 hexagonal structure is generally regarded as a detrimental phase for the tensile, corrosion and creep-rupture properties. 26,27…”
Section: Resultsmentioning
confidence: 99%
“…Both the AT1000 and AT890 samples consisted of the γ′ phase, β phase and η phase. Amongst these, (i) the γ′ precipitates acted as strengthening phase to inhibit the early crack development during creep, 30 (ii) the β-NiAl phases in GBs were demonstrated to enhance the resistance to crack propagation by preventing oxygen diffusion 31 and (iii) the plate-like η phase precipitates 26,27 were likely to be detrimental for the tensile, corrosion and creep-rupture properties. On the basis, a significant coarsening of the irregular γ′ phase would result in its decreased number density and strengthening effect, thus leading to easy crack formation in the AT1000 samples after long-term stress rupture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that according to the Ostwald ripening theory [26,27], there is a critical dimension γ lim for the coarsening of the γ phase, which depends on the content of the elements forming the γ phase in the alloy. There is another mechanism for the coarsening of the γ phase, that is γ gather and grow [28][29][30], as shown in Figure 3a yellow line circles. The dissolution temperature of γ′ phase of GH4065A superalloy is about 1119 °C [24].…”
Section: Macro-and Microstructure Characteristics Of Jointmentioning
confidence: 99%
“…However, there is a risk of eta (η) phase precipitation, known as D0 24 crystal structure (HCP), with composition Ni 3 (Ti,Nb), when Ti content exceeds the critical value [22][23][24]. It has been reported that the η phase is formed in Ni-based alloys with consumption of the γ phase, which can induce formation of the γ phase depletion zone [23,[25][26][27]. Consequently, as Ti increases, the possibility of the η phase also increases.…”
Section: Introductionmentioning
confidence: 99%